Pengaruh Pemahaman Akuntansi Koperasi Berdasarkan Standar Akuntansi Keuangan Entitas tanpa Akuntabilitas Publik, Tingkat Kompetensi, dan Sistem Pengendalian Intern terhadap Kualitas Laporan Keuangan pada Koperasi Pegawai Republik Indonesia - Sri Ayem; Mahardian Mustiko Nugroho (Faculty of Economics and Business, University of Pancasakti Tegal, 2020)
This study aims to determine the effect of understanding of cooperative accounting based on SAK ETAP, level of competence, and internal control systems on the quality of financial statements in the Cooperative Employees of the Republic of Indonesia in Purworejo Regency. This research was conducted at 11 Cooperative Employees of the Republic of Indonesia in Purworejo Regency. This study uses primary data in the form of questionnaires distributed by respondents of the cooperative in the Cooperative Employees of the Republic of Indonesia in Purworejo Regency. The number of samples in this study were 60 respondents. This research uses multiple regression analysis method by using SPSS version 18. The result of this study state that the cooperative accounting understanding based on SAK ETAP variable has a positive and significant effect on the quality of financial statements, the competency level variable has a negative and not significant effect on the quality of financial statements, and the internal control systems variable has a positive and significant effect to the quality of financial statements.